2017
DOI: 10.1002/stem.2759
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Versus-Host Disease Amelioration by Human Bone Marrow Mesenchymal Stromal/Stem Cell-Derived Extracellular Vesicles Is Associated with Peripheral Preservation of Naive T Cell Populations

Abstract: A substantial proportion of patients with acute graft-versus-host disease (aGVHD) respond to cell therapy with culture-expanded human bone marrow mesenchymal stromal/stem cells (BM-MSCs). However, the mechanisms by which these cells can ameliorate aGVHD-associated complications remain to be clarified. We show here that BM-MSC-derived extracellular vesicles (EVs) recapitulated the therapeutic effects of BM-MSCs against aGVHD. Systemic infusion of human BM-MSCderived EVs prolonged the survival of mice with aGVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 66 publications
(76 reference statements)
13
140
1
1
Order By: Relevance
“…The immunoregulatory effects exerted by SC-EVs on activated T cells remain a widely debated topic. For instance, one study observed that the co-culture of SC-EVs with peripheral blood mononuclear cells (PBMCs) specifically suppressed the proliferation of T cells, whereas it did not affect that of B cells and NK cells (71). However, other studies have reported that SC-EVs inhibited the proliferation of NK cells and B cells, although its effect on the proliferation of T cells remains unclear (30,108).…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoregulatory effects exerted by SC-EVs on activated T cells remain a widely debated topic. For instance, one study observed that the co-culture of SC-EVs with peripheral blood mononuclear cells (PBMCs) specifically suppressed the proliferation of T cells, whereas it did not affect that of B cells and NK cells (71). However, other studies have reported that SC-EVs inhibited the proliferation of NK cells and B cells, although its effect on the proliferation of T cells remains unclear (30,108).…”
Section: T Cellsmentioning
confidence: 99%
“…It has been demonstrated that SC-EVs carry a variety of active molecules, such as TGF-β (10, 92), active CD73 protein (11,79), IDO protein (88), or miR-125a-3p (71). These molecules endow SC-EVs with the ability to inhibit T cell proliferation (11,71,88,92,98,112,116,117) and activation (71,76,77,97,98,112,116), and preserve the circulating naive T cells (71) ( Table 1).…”
Section: Stem Cell-derived Extracellular Vesicle Potential In T Cellmentioning
confidence: 99%
“…In the present work, MSC-EVs have been shown to possess immunomodulatory functions which promote B cell activation, induction of Breg and B cell proliferation was compared to that the whole MSCs [57]. Fujii et al, showed EVs derived from BM-NSCs have potential therapeutic effect on acute graft versus host disease (GVHD) and indicated the EVs probably inhibit the effector T cell induction and kept circulating naïve T cells [58]. However, EV usually does not treat as well as the cell itself, and its biological effects may be affected by the surrounding microenvironment [59].…”
Section: Evs As Therapymentioning
confidence: 92%
“…The EVs isolated from patient serum contains three miRNAs (miR-423, miR-199, miR-93), which may be related to the incidence and severity of GVHD [68]; and the expression of CD146, CD31, and CD140-α on EVs surface, is also closely related to the onset of the disease [69]. Traditional MSCs therapy after replacement with EVs for GVHD also showed ideal results, suggesting that MSCs-derived EVs are potential for cell-free therapy for GVHD [58,70]. Kordelas L et al used MSCs-derived EVs instead of MSCs in the patient with GVHD, and the promising results were obtained.…”
Section: Evs As Therapymentioning
confidence: 99%
“…Preclinical studies have confirmed that SC-EVs can wield immunomodulatory effects in the treatment of various diseases by transporting noncoding RNAs, cytokines, and other immunomodulatory molecules. Fujii et al showed that human BMSC-EVs reduced the ratio of CD62L-CD44+/CS62+CD44-T cells in graft-versus-host diseased mice and prolonged their survival by transporting miR-125a-3p [76]. Li et al showed that hucMSC-EXs reduced inflammation in burned rats by inhibiting the expression of Toll-like receptor 4 in macrophages [77].…”
Section: Immune Regulationmentioning
confidence: 99%